A new species of the subterranean genus Troglocyphoniscus Strouhal, 1939 (Isopoda: Oniscidea: Trichoniscidae) from the Tara Mountain, Serbia - Karaman, Ivo; Horvatović, Mladen (Zootaxa, 2026)
Troglocyphoniscus tarae sp. nov. was described from the Medveđa jama cave on Tara Mountain in Serbia as the fourth species in this subterranean genus. The diagnostic characteristics and affinity of the new species and genus are discussed. The distribution of the closely related troglobite genera Troglocyphoniscus and Graeconiscus is presented and discussed in the light of Mediterranean geotectonic events.